Anticancer activity of Ficus deltoidea and Tualang honey on oral cancer cells: An in vivo study / May Ameen Saeed Alkoshab - May Ameen Saeed, Alkoshab (2020)
The use of natural products have been gaining interest, notably in the area of cancer therapy and in this study, natural products rich in antioxidants such as Tualang Honey (Malaysian wild local honey) and Ficus deltoidea (Malaysian local herbal plant), were selected to assess their chemo-preventive and chemotherapeutic activities on oral cancer. The aim of this study is to evaluate the chemo-preventive and chemotherapeutic activities of Ficus deltoidea (FD) and Tualang Honey (TH) in an animal model induced for oral cancer using 4-Nitroquinoline1-oxide (4NQO). A total of 70 male Sprague-Dawley (SD) rats were distributed into ten groups (n=7 per group); Group 1, (untreated group), Group 2, (control cancer group) received 4NQO only during 8 weeks in drinking water. Groups 3, 4, 5 and 6 (chemo-preventive) received 4NQO for 8 weeks and were simultaneously treated with FD extract at 250 and 500 mg/kg and TH at 1000 and 2000 mg/kg respectively by oral gavage. Group 7, 8, 9 and 10 (chemotherapeutic) received 4NQO for 8 weeks followed by the administration of FD extract at 250 and 500 mg/kg and TH at 1000 and 2000 mg/kg respectively, for another 10 weeks. All rats from all experiments were sacrificed after 22 weeks, and the histopathological changes and incidence of oral cancer were microscopically evaluated. An immunohistochemical evaluation was conducted to determine the effects of the FD extract and TH on the expression of tumour markers; cyclin D1, bcl2, p53, β- catenin and e-cadherin using a computerised image analyser system, while the RT2 Profiler PCR Array method was employed in this study for gene expression analysis of TP53, RAC1, COX-2, TWIST 1, CCND1 and EGFR. The results of the present study showed a beneficial regression effect of the FD extract and TH on tumour progression, especially in the chemo-preventive groups. The FD extract and TH significantly reduced the incidence of oral squamous cell carcinoma (OSCC) iv from 100% to 14.3% in the high dose groups. The immunohistochemical analysis showed that the FD extract and TH had significantly decreased the expression of the key tumour marker cyclin D1 and had significantly increased the expression of the β-catenin and ecadherin proteins that are associated with enhanced cellular adhesion. Based on the gene expression analysis, TH and FD extract had reduced the expression of the TWIST1 and RAC1 genes associated with epithelial-mesenchymal transition (EMT) and had significantly downregulate the COX-2 and EGFR genes associated with cancer angiogenesis, metastasis and chemo resistance. In conclusion, our data suggest that the FD extract and TH exert chemopreventive and chemotherapeutic activities in an animal model induced for oral cancer using 4NQO and thus, have the potential to be developed as chemo-preventive and chemotherapeutic agents